The Papanicolaou Society of Cytopathology System for Reporting Pancreaticobiliary Cytology Definitions, Criteria and Explanatory Notes - Pitman, Martha Bishop; Layfield, Lester James; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This textbook/atlas is designed to present a comprehensive and state of the art standardized approach to the cytologic diagnosis and reporting of pancreaticobiliary lesions. Chapters address each of the diagnostic categories proposed by the Papanicolaou Society of Cytopathology (PSC). The definition of each category along with the specific entities contained within the category are discussed along with cytologic criteria for inclusion within the category. Each chapter is lavishly illustrated demonstrating the diagnostic criteria. Additionally, appropriate ancillary testing and current management for entities in the category are briefly discussed. Sample diagnostic reports are provided for each category. The Papanicolaou Society of Cytopathology System for Reporting Pancreaticobiliary Cytology will provide the reader with a unified approach to diagnosing and reporting cytologic specimens obtained from the pancreaticobiliary tract. This text will serve as a reference guide for pathologists, surgeons, endoscopists and radiologists.
Overview of Diagnostic Terminology and Reporting -- Category I: Non-Diagnostic -- Category II: Negative (for Malignancy) -- Category III: Atypical -- Category IV: Neoplastic-Benign -- Category IV: Neoplastic-Other -- Category V: Suspicious (for Malignancy) -- Category VI: Positive or Malignant -- Appendix A: Template for Cyst Diagnosis -- Appendix B: Mucinous Etiology -- Appendix C: Useful Ancillary Tests.
Keywords: Medicine; Gastroenterology; Pathology; Medicine & Public Health; Pathology; Gastroenterology; Electronic books